Improving biosecurity practices of finfish aquaculture in Bangladesh - Rheman, Shafiq; Hossain, Sabrina (WorldFish, 2023)
Finfish biosecurity in Bangladesh is a growing concern due to the high demand for fish and the increasing prevalence of diseases in aquaculture. WorldFish and partners are working with Bangladesh national research institutions and national competent authorities to design and develop finfish biosecurity training modules to reduce antimicrobial use (AMU) and antimicrobial resistance (AMR) burden in commercial finfish aquaculture systems. Through an 8-day participatory pilot program in February 2023, collaborative partners identified major pathogen-spread pathways, current biosecurity practices and gaps in commercial finfish aquatic production systems.